(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Masturbation is a topic of discussion among all the categories of people since ancient times. Masturbation refers to non-penetrative sexual stimulation of a person’s genitals, often to the point of orgasm. The stimulation can be performed manually, by other types of bodily contact (short of sexual contact), by use of objects or tools, or by some combination of these methods. Masturbatory habits amounting to masturbatory abnormalities are included in the Chapter V (F 65.8) of International Statistical Classification of Diseases and Related Health Problems – 10 under “Other disorders of sexual preference”. In later 1700, a forged association was made between masturbation and mental illness. Masturbation served for decades as catch all diagnosis for all types of medical complaints of uncertain etiology. During the late 19th century, investigations in psychology and sexology made it clear that masturbation is nearly universal. In Sanskrit, semen is known as ‘DHAT’; and in Susruta Samhita the disorder related to loss of this DHAT has been mentioned as ‘Shukrameha’ and also known as Dhat Syndrome. Kissing, masturbation and intercourse are the frequent sexual activities among adults. Even after a permanent sexual relationship has been established, masturbation remains as a healthy practice during the illness or absence of partner or when intercourse is unsatisfactory. In older age group Involuntary Masturbation may be a manifestation of stroke related Alien Hand Syndrome. Today, masturbatory act is considered as a healthy practice when done in private and an offence if done in the public in most of the countries.